Analisis Deiksis dalam Film Cocaine Bear (2023) - Karina Dilla Indrianing; Senowarsito; Nur Hidayat (Melati Institute, 2023)
This study aims to determine the types of deixis and references used by the main character in the COCAINE BEAR (2023) movie, and to determine the dominant deixis used by the main character in COCAINE BEAR (2023) movie. The study employs qualitative methods to gather data from the main character’s spoken sentences from the COCAINE BEAR (2023) movie, which were downloaded from the internet. According to the study's results, 608 deixis expressions were utilized. The expressions are divided into five deixis, 397 person deixis, 29 place deixis, 2 time deixis, 5 social deixis, 24 discourse deixis. The references found in this study are, first person deixis found are “I”, “me”, “my”, “we”, and “our”; as the second person deixis are “you” and “your”; and these words are found in third person deixis, namely “it”, “she”, “he”, “him”, and “they”. Words are found in place of deixis; “here”, “there”, “that”, and “this.”. Words like “now”, and “weekend”, can be found in time deixis. These words are found in social deixis, “Dad” and “your mother”. The last discourse deixis found is “that” and “this”. The dominant deixis used by the main character in the film COCAINE BEAR (2023) is persona deixis.